Incidence and predictors of neonatal hyperbilirubinemia requiring phototherapy: A prospective cohort study at a tertiary hospital in Uganda - Hamdi Mohamed Yusuf; Munanura Turyasiima; Jolly Nankunda; Sabinah Wesigemukama Twesigemukama; Walufu Ivan Egesa; Abdullahi Mohamed Abdulle; Walyeldin Elfakey; Zakaria Abdi Said; Ahmed Hassan Mohamud; Joshua Epuitai; Feisal Dahir Kahie; Hanan Asad Hassan; et al. (PLoS ONE, 2026)
Background Neonatal hyperbilirubinemia remains a leading cause of preventable neurological impairment and death in low-resource settings, particularly in sub-Saharan Africa. Despite its burden, data on incidence and risk factors in Uganda are limited. This study aimed to determine the incidence and predictors of hyperbilirubinemia among neonates at a Ugandan referral hospital. Methods A prospective cohort study was conducted at Mubende Regional Referral Hospital from November 2024 to February 2025. A total of 539 mother-infant pairs were enrolled, with 534 completing follow-up. Neonates were followed from birth up to 7 days of life. Data on maternal and neonatal characteristics were collected through interviews and medical records. Laboratory tests included total serum bilirubin and ABO/Rh blood grouping. Modified Poisson regression was used to identify independent predictors of hyperbilirubinemia, with statistical significance set at p < 0.05. Results The risk of hyperbilirubinemia requiring phototherapy was increased by close to two times among neonates born to mothers who were underweight, overweight, or obese (based on maternal BMI during pregnancy) (aIRR = 1.703, CI = 1.082–2.680, P = 0.021; aIRR = 1.916, CI = 1.447–3.183, P < 0.001; aIRR = 1.930, CI = 1.233–3.022, P = 0.004), those from households with monthly income <200,000 UGX (aIRR = 1.798, CI = 1.306–2.477, P < 0.001), those delivered by cesarean section (aIRR = 1.835, CI = 1.291–2.610, P = 0.001), and those with premature rupture of membranes (PROM) ( aIRR = 1.538, CI = 1.109–2.132, P = 0.010). The risk of hyperbilirubinemia requiring phototherapy was increased by over two times for the preterm (aIR = 2.776, CI = 1.978–3.895, P < 0.001), those in whom feeding was initiated after 1 hour (aIRR = 2.145, CI = 1.411–3.261, P < 0.001), instrumental delivery (aIRR = 2.005, CI = 1.109–3.625, P = 0.021) and ABO incompatibility (aIRR = 2.985, CI = 2.060–4.325, P < 0.001). Conclusion 2 in 10 neonates developed hyperbilirubinemia requiring phototherapy. The condition was associated with both modifiable factors, such as delayed initiation of breastfeeding, and non-modifiable factors, including ABO incompatibility, prematurity, and mode of delivery.